siRNA Targeting Mcl-1 Potentiates the Anticancer Activity of Andrographolide Nanosuspensions via Apoptosis in Breast Cancer Cells - Supusson Pengnam; Purin Charoensuksai; Boon-ek Yingyongnarongkul; Rungnapha Saeeng; Hasan Uludağ; Prasopchai Patrojanasophon; Praneet Opanasopit; Samarwadee Plianwong (MDPI AG, 2022)
Breast cancer is the second leading cause of cancer-related death in the US. However, recurrence is frequently found despite adjuvant therapy being available. Combination therapy with cytotoxic drugs and gene therapy is being developed to be a new promising cancer treatment strategy. Introducing substituted dithiocarbamate moieties at the C12 position of andrographolide (3nAG) could improve its anticancer selectivity in the MCF-7 breast cancer cell line. However, its hydrophobicity is one of its main drawbacks. This work successfully prepared 3nAG nanosuspension stabilized with the chitosan derivative NSC (3nAGN-NSC) to increase solubility and pharmacological effectiveness. siRNAs have emerged as a promising therapeutic alternative for interfering with particular mRNA. The 3nAGN-NSC had also induced Mcl-1 mRNA expression in MCF-7 human breast cancer cells at 8, 12, and 24 h. This indicates that, in addition to Mcl-1 silencing by siRNA (siMcl-1) in MCF-7 with substantial Mcl-1 reliance, rationally devised combination treatment may cause the death of cancer cells in breast cancer. The Fa-CI analysis showed that the combination of 3nAGN-NSC and siMcl-1 had a synergistic effect with a combination index (CI) value of 0.75 (CI < 1 indicating synergistic effects) at the fractional inhibition of Fa 0.7. The synergistic effect was validated by flow cytometry, with the induction of apoptosis as the mechanism of reduced cell viability. Our findings suggested the rational use of 3nAGN-NSC in combination with siMcl-1 to kill breast cancer cells.